2019
DOI: 10.17691/stm2019.11.4.14
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Parameters of Magnetron Sputtering on the Structure and Chemical Composition of Titanium Alloy Implant Surfaces

Abstract: The aim of the investigation is to study the influence of different parameters of magnetron sputtering on the structure and chemical composition of titanium and titanium alloy surfaces used for endosseous implantation. Materials and Methods. The study involved the use of the NSC-3500 magnetron sputtering system (NANO-MASTER Inc., USA) providing the possibility to obtain coatings of almost any metals, alloys and semiconductors materials without a shift in the stoichiometric composition. High-purity argon (99.99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The method of magnetron sputtering is widely used to obtain biocompatible coatings on implants [3][4][5][6]. By applying various modes of magnetron sputtering, one can influence the structure and chemical composition of the surfaces of titanium and its alloys used for intraosseous implantation [6].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The method of magnetron sputtering is widely used to obtain biocompatible coatings on implants [3][4][5][6]. By applying various modes of magnetron sputtering, one can influence the structure and chemical composition of the surfaces of titanium and its alloys used for intraosseous implantation [6].…”
mentioning
confidence: 99%
“…The method of magnetron sputtering is widely used to obtain biocompatible coatings on implants [3][4][5][6]. By applying various modes of magnetron sputtering, one can influence the structure and chemical composition of the surfaces of titanium and its alloys used for intraosseous implantation [6]. It was found that an increase in the sputtering power (from 200 to 300 W) leads to a significant change in the structure, which is accompanied by a change in the grain size and, as a result, in the surface roughness.…”
mentioning
confidence: 99%
See 1 more Smart Citation